Characteristic of Subcutan Mycosis: A Retrospective study - Netty Sukmawati; Evy Ervianty (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Subcutaneous mycosis is a rare cases. Incidence of subcutaneous mycosis in Indonesia is unknown. Limited experiences, problems in diagnosis and management may cause difficulties in treating subcutaneous mycosis. Objective: To know the characteristic of subcutaneous mycosis cases in Indonesia and to improve the quality of medical service. Methods: Retrospective study of cases were treated in Departement of Dermatology and Venereology Dr. Soetomo General Hospital within 2010–2014 (5 years). The data include number of cases, age, sex, domicile, complained, risk factors, duration of illness, location of skin lesion, symptoms, laboratory examination, and treatment. Results: a number of cases ranged between 1-8 patients per year. There was 1 case in 2010, 2 cases in 2011, 2 cases in 2012, 2 cases in 2013, and 8 cases in 2014. The diagnosis included eumycetoma, actinomycetoma, chromoblastomycosis, basidiobolomycosis, and phaeohyphomycosis. No cases of sporotrichosis, lobomycosis, and rhinosporodiosis. Majority of patients showed specific characteristic history, clinical manifestation, and histopathology examination, but most culture results were negative. Treatment was given based on diagnosis. Conclusions: Number of subcutaneous mycosis cases per year is 1-8 patients. Diagnosis based on characteristic history, clinical manifestations and histopathology examination.Key words: mycosis subcutan, characteristic, retrospective study.